Madrasah Menghadapi Tantangan Globalisasi - Solihatudiniyah, Lela Salamah; Suhendi, Saca (Journal of Citizen Research and Development, 2025)
Madrasah as an Islamic educational institution has a strategic role in maintaining Islamic values while preparing a generation that is able to compete in the era of globalization. This article aims to explore the challenges faced by madrasahs amidst globalization and strategies that can be applied to improve their competitiveness and relevance. This study uses a qualitative approach with literature study methods and in-depth interviews, which show that madrasahs face major challenges in the fields of technology, curriculum, and graduate competencies. The implementation of technology-based strategies, global collaboration, and curriculum updates are the keys to the success of madrasahs in facing the global era. Thus, madrasahs are expected to be able to adapt and contribute significantly to education at the national and international levels.